Effects of aggregate and interface characteristics on chloride diffusion in concrete based on 3D random aggregate model. (3rd January 2022) - Yu, Lei; Liu, Chunhui; Mei, Hua; Xia, Yu; Liu, Zhen; Xu, Feng; Zhou, Cuiying
Graphical abstract: Highlights: The 3D concrete model with aggregates and interfacial transition zone is modeled. The increase of aggregate volume ratios inhibited the chloride diffusion. The aggregate volume ratio for back calculation has an important influence on model. Different interfacial transition zone thickness is no influence on the model accuracy. The reason for the better chloride resistance of nanocomposite concrete is studied. Abstract: The chloride diffusion in concrete with different aggregate volume ratios (AVR) and interfacial transition zone (ITZ) were studied in this paper. According to the finite element method, the 3D concrete model with aggregates and ITZ is modeled, and the chloride diffusion characteristics were numerically simulated and compared with the experimental results. Furthermore, the reasons for the better chloride resistance of nanocomposite concrete are studied. The results show that the established model can well reflect the material properties of concrete and has a good application effect on chloride diffusion. The increase of AVR inhibited the chloride diffusion and there is significant influence on the simulation results when use different AVR to back calculation. However, it is little influence on the simulation results when change the ITZ condition of back calculation. The better chloride diffusion resistance of nanocomposite concrete is mainly due to the improved anti-diffusion properties of the ITZ.